Proposed Marketing Strategy for Talanoa Kopi and Space - Nadila Estelita Putri G; Atik Aprianingsih (PT. Publikasiku Academic Solution, 2025)
Indonesia's economy relies heavily on Micro, Small and Medium Enterprises (MSMEs), which contribute greatly to GDP and employment. Among them, the food and beverage (F&B) industry has experienced tremendous growth, driven by consumer trends and the increasing popularity of coffee. The purpose of this study is to suggest strategies to improve the competitiveness of Talanoa Kopi and Space, a coffee shop located in Cibubur, by increasing brand awareness, consumer attitudes, and purchase intention. Structural Equation Modeling Partial Least Squares (SEM-PLS) was used to test the hypotheses regarding Marketing Mix, Brand Awareness, Consumer Attitude, and Purchase Intention in this study, which used a quantitative approach. The results show that Customer Attitude and Purchase Intention are substantially influenced by Brand Awareness, both directly and through mediation. In the same way, Marketing Mix affects Customer Attitude, but its effect on Purchase Intention is mediated by Customer Attitude. These observations underscore the importance of improving brand recognition and adjusting marketing strategies to meet consumer expectations. Proposed business solutions include implementing a multi-channel ordering system, launching a loyalty program, diversifying product offerings, and improving customer experience through innovative services and interactive engagement. This research contributes to the academic understanding of the interaction between marketing variables and consumer behavior while providing actionable recommendations for MSMEs in the food and beverage sector. Future research can explore similar frameworks in different contexts to validate these findings and increase generalizability.